Self-Assembly of Asymmetrically Functionalized Titania Nanoparticles into Nanoshells - Svensson, Fredric G. (Materials (Basel), 2020)
Titania (anatase) nanoparticles were anisotropically functionalized in water-toluene Pickering emulsions to self-assemble into nanoshells with diameters from 500 nm to 3 μm as candidates for encapsulation of drugs and other compounds. The water-phase contained a hydrophilic ligand, glucose-6-phosphate, while the toluene-phase contained a hydrophobic ligand, n-dodecylphosphonic acid. The addition of a dilute sodium alginate suspension that provided electrostatic charge was essential for the self-limited assembly of the nanoshells. The self-assembled spheres were characterized by scanning electron microscopy, elemental mapping, and atomic force microscopy. Drug release studies using tetracycline suggest a rapid release dominated by surface desorption.